Perioperative Myocardial Damage and Heart Failure in Noncardiac Surgery. Part 1. Etiopathogenesis and Prognosis of Perioperative Cardiac Complications (Review) - I. A. Kozlov; A. M. Ovezov; E. L. Petrovskaya (Общая реаниматология, 2019)
The purpose of this paper is to provide scientific and practical information on assessment of the risk of myocardical damage development after noncardiac operations (NOMD): ischemia or myocardial infarction (MI), and/or heart failure (HF) and their prevention in adult patients. This overview of literature consists of two parts. The first part analyzes epidemiology, etiopathogeneis, and POCC risk prediction methods; the second part describes the possibilities of adjuvant pharmacological cardioprotection and approaches to optimizing anesthesiological support of operative interventions in high cardiac risk patients.The problem of perioperative cardiac complications in noncardiac surgey is one of relevant complex issues of contemporary medicine. In line with contemporary views, NOMD is now regarded as a separate variant of a pathological process in the heart muscle. According to extensive studies, about 40% of mortality of adult patients during non-cardial operative inverventions are caused by various NOMD and/or HF. The problem under discussion is particularly relevant when medical assistance is rendered to elderly patients.